2001
DOI: 10.1002/cd.5
|View full text |Cite
|
Sign up to set email alerts
|

Children with Attention-Defecit/Hyperactivity Disorder: Peer Relationships and Peer-Oriented Interventions

Abstract: Children with attention‐defecit/hyperactivity disorder experience numerous peer difficulties and may benefit from specially designed intervention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 66 publications
3
128
1
6
Order By: Relevance
“…Several different types of social skills training have been applied to ADHD populations (e.g., Mrug, Hoza, & Gerdes, 2001). The purpose of this training is to directly teach the basic social skills children need to interact more effectively with their peers (Mrug et al, 2001).…”
Section: Social Skills Training Almost All Interventions Targeting Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Several different types of social skills training have been applied to ADHD populations (e.g., Mrug, Hoza, & Gerdes, 2001). The purpose of this training is to directly teach the basic social skills children need to interact more effectively with their peers (Mrug et al, 2001).…”
Section: Social Skills Training Almost All Interventions Targeting Pmentioning
confidence: 99%
“…Several different types of social skills training have been applied to ADHD populations (e.g., Mrug, Hoza, & Gerdes, 2001). The purpose of this training is to directly teach the basic social skills children need to interact more effectively with their peers (Mrug et al, 2001). However, the consensus by this point is that clinic-based social skills training have not proven effective for children with ADHD , possibly because it is difficult, if not impossible, to work on peer relationships in the office or in the classroom (Pelham, Fabiano, Gnagy, Greiner, & Hoza, 2005).…”
Section: Social Skills Training Almost All Interventions Targeting Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas earlier studies (e.g., Cunningham, Siegel, & Offord, 1985) suggested that inattentiveness may be a factor limiting opportunities for observational learning of social skills in children with ADHD, more recent work focuses on performance deficits (Barkley, 2000). Further, it is now widely accepted that a major contributing factor to the peer problems of children with ADHD is their largely unrestrained, overbearing interaction style, characterized by hyperactivity, aggression, bossiness, and other forms of controlling behavior that make them highly aversive to peers (see Mrug et al, 2001;Whalen & Henker, 1992, for reviews).Stimulant medication is useful for reducing rates of these negative and controlling behaviors (Cunningham et al, 1985) but typically yields few corresponding increases in positive behaviors (see Landau &Moore, 1991, andHenker, 1991, for reviews). Nonetheless, laboratory studies requiring normal peers to rate videotaped behavior of children with ADHD in both medicated and unmedicated states suggest that medication-related improvements in behavior are quite apparent to nondeviant peers even after short periods of observation (e.g., 15 min; Whalen, Henker, Castro, & Granger, 1987).…”
mentioning
confidence: 99%
“…While five conjoint parent sessions were incorporated into the therapy, these did not appear to include parent training. Teacher and parent behavioral consultation and training may have also helped enhance gains (Mrug, Hoza, & Gerdes, 2001;Pfiffner & McBurtnett, 1997 …”
Section: Possible Undiagnosed Adhdmentioning
confidence: 99%